2012
DOI: 10.1016/j.ijgo.2011.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Median levels of serum biomarkers of fetal Down syndrome detected during the first trimester among pregnant Thai women

Abstract: Ethnic group-specific medians for PAPP-A and free β-hCG should be incorporated during first-trimester screening for fetal Down syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
1
9
2
Order By: Relevance
“…However, our results also differed from a study in northern Thailand [9], which found significantly higher levels of both maternal serum markers compared to our study. The assays in the northern Thailand study [9] were performed using the DELFIA Xpress Immunoanalyzer System (Perkin Elmer, Waltham, MA, USA).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, our results also differed from a study in northern Thailand [9], which found significantly higher levels of both maternal serum markers compared to our study. The assays in the northern Thailand study [9] were performed using the DELFIA Xpress Immunoanalyzer System (Perkin Elmer, Waltham, MA, USA).…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results also differed from a study in northern Thailand [9], which found significantly higher levels of both maternal serum markers compared to our study. The assays in the northern Thailand study [9] were performed using the DELFIA Xpress Immunoanalyzer System (Perkin Elmer, Waltham, MA, USA). The very high values of r for each prediction equation from northern Thailand [9] indicate that the equations were constructed by regressing the daily medians of the measured values against gestational age.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations